PERLAWANAN MUSISI GAMBANG KROMONG TERHADAP DOMINASI INDUSTRI MUSIK MAINSTREAM - Kasyfiyullah; Hafidz Alfian (Emerald: Journal of Economics and Social Sciences, 2023)
This research analyzes the efforts of gambang kromong musicians as a traditional music that has begun to be forgotten and eroded by the rapid development of the music industry. By using Anthony Giddens' structuration theory, this research will explain how the social practices that occur between the gambang kromong musicians as agents with the culture of public taste and the gambang kromong music standard as the structure. using qualitative research methods with interviews and observations as data collection techniques. The results show that the preservation of gambang kromong music becomes an awareness of the musicians as agents who produce an agency by using the enabling side of the existing structure. Social practice through 'music re-creation' is carried out by continuing to highlight the characteristics and identity of this music in its combination with global cultural elements as a form of exploration and innovation as well as a form of active resistance the dominating effects of the mainstream music industry.